Mafia in the Mirror of Sociology - Вадим Викторович Волков (Journal of Economic Sociology, 2010)
Mafia is the most popular topic in the cinema and literature. The paper covers the historical and cultural background of mafia and its cultural and organizational forms. Particularly it tells about Italian and American mafias. The research is based on the sociological assumptions